Efeito da sincronização e indução do estro e do desmame precoce sobre a performance reprodutiva de ovelhas deslanadas e no desempenho dos cordeiros. - Costa, Ludmilla Béliche Alves (2009)
The aim of this study was to evaluate the effects of synchronization/estrus induction and the early weaning in the reproduction performance the hairless ewes and the lambs performance.For this was development two studies. The first tested two treatment of synchronization with the conventional method with 14 days of progestagen application (long-term method=TL) and the short-term with use implants for five days (short-term method= TS) on the estrus incidence, synchronization degree, pregnancy and birth rate of hairless ewes. The second study was the aim evaluate the effect of early weaning (EW), with 45 days of age, in relation to the traditional weaning (WT),with 90 days, on post-weaning performance growth rate of lambs, raised in semi-intensive system. The first study was use 19 hairless ewes, being 9 ewes for TL and 10 ewes for TS. All ewes were synchronized with intravaginal implant impregnated with 60 mg of Medroxiprogesterona Acetate (MAP) inserted in the cranial portion of the vagina and after the sponge removal, was applied equine chorionic gonadotrophin (eCG). Estrus was detected by vasectomized ram every 4 hours, after 24 h of the sponge removal, and those ewes that were detected in estrus were mated with an entire ram, 12 hours after the detection. The pregnancy diagnosis was done by ultrasonografic 45 days after mating. Data were analyzed by the procedure of the Lineal General Model (GLM) of the SAS program, to estimate the percentage of females in estrus, time of interval among end of treatment and beginning of the estrus (FT-IE) and the percentage of pregnancy. The synchronization precision between interval among end of treatment and beginning of the estrus was verificaty using q-quadratic test analysing the percentage of ewes in estrous in terval to 8 h (± 4h the modal in the experimental groups). From the total ewes synchronized, 84,2% showed estrus, with the TL method showing 88,8% and the TS 80,0%, without significant difference between treatments (P>0,05). The ewes of the TS group showed a significant (P <0,05) largest interval among FT-IE (51,25 ± 14,1), in relation to TL (36,87 ± 8,54). Pregnancy rate and birth was similar in both group of ewes, with average of 62,5%. The second study was use 32 lambs, 22 lambs, being 11 males and 11 females in EW and 10 lambs, where 4 were male and 6 females for WT. The effect of weaning age in the subsequent growth rate of lambs was evaluated through liveweight every two weeks from weaning to 180 days of age. The data of win weigth was analyzed through procedure of the General Lineal Model (GLM) of SAS and means was compare of Tukey test in 5% of probability. The effect of sex in win weigth of lambs was analyzed by ANOVA the procedure of the General Lineal Model (GLM) of SAS. The regression analysis by relation of live weigth (y in Kg) with age (x in days) was analyzed procedure GLM to second degrees (P<0,01).The results show that early-weaning had not significant effect (P>0.05) on post-weaning growth weight. Have significant effect (P<0.01) for weigth body between sexs in early weaning lambs. It was concluded that short hormonal treatement was effective to obtain estrus synchronization, hairless ewes, and the semi-intensive system, weaning it of lambs with 45 days of age it constitutes a handling alternative to improve the lamb production.